2023
DOI: 10.1007/s00787-023-02264-y
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of self-injury in adolescence: a systematic review and meta-analysis

Abstract: In the past 10 years, there has been a growing interest in self-injurious behavior (SIB) among adolescents. The lifetime prevalence of SIB is between 16 and 22% in community sample with females more likely to engage in SIB. There are conflicting results about the global distribution of the prevalence of SIB and whether the SIB has increased in the 21st century. Our aim in the current study was to conduct a systematic search of and meta-analysis on the prevalence of SIB in adolescents over the past 5 years’ wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 124 publications
(71 reference statements)
0
5
0
Order By: Relevance
“…The lifetime prevalence of self-injurious behaviors both with and without suicidal intent has been reported at 20% in a meta-analytical study investigating the global prevalence of self-harming behaviors in adolescents [34]. Farkas et al (2023) revealed in their recent systematic review and meta-analysis an overall prevalence of NSSI of 16% in studies published between 2015 and 2020. Noteworthy gender differences in prevalence rates were also reported, with a prevalence rate of approximately 21% for females and 16.5% for males [35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lifetime prevalence of self-injurious behaviors both with and without suicidal intent has been reported at 20% in a meta-analytical study investigating the global prevalence of self-harming behaviors in adolescents [34]. Farkas et al (2023) revealed in their recent systematic review and meta-analysis an overall prevalence of NSSI of 16% in studies published between 2015 and 2020. Noteworthy gender differences in prevalence rates were also reported, with a prevalence rate of approximately 21% for females and 16.5% for males [35].…”
Section: Introductionmentioning
confidence: 99%
“…Farkas et al (2023) revealed in their recent systematic review and meta-analysis an overall prevalence of NSSI of 16% in studies published between 2015 and 2020. Noteworthy gender differences in prevalence rates were also reported, with a prevalence rate of approximately 21% for females and 16.5% for males [35]. A 90% prevalence of internet use has been reported among adolescents that employ self-injurious acts [36].…”
Section: Introductionmentioning
confidence: 99%
“…Recent meta-analytic work stated how the occurrence of NSSI behaviour during development shows an initial increase in correspondence of early adolescence, followed by a peak and a subsequent decline ( 3 ). Reported data sums up to a relatively high prevalence in this population, estimated to be 16% ( 4 ), and, as such, NSSI is identified as a major public health concern ( 5 , 6 ), even more so as it associates with different negative outcomes, including suicidal behaviours ( 7 ). Suicidal behaviours are defined as nonfatal suicidal thoughts and behaviours and classified as a) suicide ideation, the presence of thoughts of ending one’s life; b) suicide plans, the formulation of a specific method to do so; c) suicide attempts (SA), which refer to potentially self-injurious behaviours in which there is at least some intent, overt or inferred, to die ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recognized as a transdiagnostic entity, NSSI has been proposed as a potential disorder warranting additional research in the Diagnostic and Statistical Manual of Mental Disorders (Fifth Edition) (DSM-5) . Global prevalence estimates of NSSI among adolescents are approximately 16 to 17% . NSSI behaviors include cutting, scratching, burning, and striking or punching objects to cause bruising or bleeding .…”
Section: Introductionmentioning
confidence: 99%
“…3 Global prevalence estimates of NSSI among adolescents are approximately 16 to 17%. 4,5 NSSI behaviors include cutting, scratching, burning, and striking or punching objects to cause bruising or bleeding. 6 Notably, NSSI is a significant predictor of subsequent suicide attempts.…”
Section: Introductionmentioning
confidence: 99%